Corporate Social Responsibility (CSR) PT Djarum in Improving the Quality of life of the Community in Kudus Regency 1986-1998 - Risanti, Imma Ghoida; Shokheh, Mukhamad (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
The dynamic and ever-growing economic conditions of Indonesia have created an important context in the relationship between the economy and CSR. This study aims to describe and analyze two main issues: 1) the origins of PT Djarum and the establishment of CSR through the Djarum Foundation, and 2) the role of CSR at PT Djarum and its impact on the quality of life for the community in Kudus from 1986 to 1998. This research uses historical research methods, applying steps that include heuristics (source collection), source criticism (analysis of the validity and reliability of sources), interpretation (interpretation of the meaning of historical data), and historiography (writing history). The results of this study show that PT Djarum's CSR activities have had a significant impact on improving the standard of living of the Kudus community. Scholarship programs, social assistance, athlete training, cultural preservation, and environmental conservation not only strengthen the relationship between the company and the community but also form a positive image of the company in the long term. Thus, PT Djarum's CSR in the New Order era was not only a business strategy but also a form of the company's moral and social responsibility toward local community development.